Effects of Low-level Laser Therapy on Fibroblast Density in Achilles Tendon Rupture Healing - Cakra Andhika; Raden Andri Primadhi; Hermawan Nagar Rasyid (Faculty of Medicine Universitas Padjadjaran, 2021)
Objective: To investigate the effect of low-level laser therapy (LLLT) on fibroblast proliferation as a part of the tendon healing cascade. Methods: This was an unpaired comparative experimental animal laboratory study with one control groups and two experimental groups, each consisted of 10 Sprague Dawley rats. The experimental groups 1 and 2 were given infrared irradiation for 15 minutes and 30 minutes per day, respectively, after having their achilles tendon partially cut. Histological assessment was carried out to assess the fibroblast density in healing site after three weeks on intervention. Results: The median values of fibroblast density in group 1, group 2, and control group were 1, 2, and 1, respectively, with a p-value of 0.014. No significant difference (p = 0.123) was identified on Mann-Whitney test between the fibroblast density of group 1 and group 2. The same was also true forgroup 1 and control group (p = 0.315). A significant difference was found between group 2 and control group (p = 0.005). Conclusions: A regime of LLLT irradiation of 30 min/day for two weeks (1080 J cm-2) improves the fibroblast proliferation amidst tendon healing in a partially injured achilles tendon in a rat model, which is not seen in the regime with a 15 min/day duration. This emphasizes the significance of irradiation time to improve tendon healing, despite the deficient understanding of the mechanism.